Respuesta :

Raaida
First, find f(x+h) = (-9/(x+h)) ... just substitue (x+h) for every x.

Then plug in f(x+h) and f(x) in the difference quotient formula.

Lim/h->0\ [f(x+h) - f(x)]/h

Or, [(-9/ (x+h)) - -9/x] /h
Or, [(-9/ (x+h)) + 9/x]/h
Or, [(-9x + 9x + 9h)/ x(x+h)] / h
Or, [9h / (x^2 + hx)]/h .............................................. add like terms
Or, ( 9h / (x^2 + hx)) * h/1 .................divide by 7 is equivalent to multiply by 1/7
Or, 9/ (x^2 + hx) .................................cancle out the h
Or, 9/ x^2 ........................................... plug in 0 for h

Now, the function asks for x=6, so we plug in 6 for every x
so, the limit = 9/ 6^2 = 9/36 = 1/4.

The derivative of [tex]f(x) = \frac{9}{x}[/tex] evaluated at [tex]x = 6[/tex] is [tex]-\frac{1}{6}[/tex].

In this question, we will use the Derivative Rules and the direct Evaluation of the resulting Function at a given value of [tex]x[/tex]. Let [tex]f(x) = \frac{9}{x}[/tex], which is equivalent to [tex]f(x) = 9\cdot x^{-1}[/tex], so that the following Derivative Rule:

[tex]\frac{d}{dt} (x^{n}) = n\cdot x^{n-1}[/tex], [tex]n \ne 0[/tex] (1)

Hence, we find that the derivative of [tex]f(x)[/tex] is:

[tex]f'(x) = -9\cdot x^{-2}[/tex]

[tex]f'(x) = -\frac{9}{x^{2}}[/tex]

If we know that [tex]x = 6[/tex], then the derivative of the function is:

[tex]f'(6) = -\frac{9}{6^{2}}[/tex]

[tex]f'(6) = -\frac{9}{36}[/tex]

[tex]f'(6) = -\frac{1}{4}[/tex]

The derivative of [tex]f(x) = \frac{9}{x}[/tex] evaluated at [tex]x = 6[/tex] is [tex]-\frac{1}{6}[/tex].

Please see this related question: https://brainly.com/question/21202620

Ver imagen xero099
ACCESS MORE